The Science of Trituration (Homoeopathy for All, 2025)
It is well known that the primary condition for a substance to be used as oral medicine that it must get dissolved in aqueous or alcoholic medium so that the solution can be absorbed in the gut to find its way into the blood stream. Our mother tinctures or liquid potentised medicines are all in the form of hydro-alcoholic solutions and thus are acceptable to our biological system. One may question here that the substances used as our food are ordinarily insoluble in water or alcohol then how they are absorbed in our gut. These substances though are ordinarily insoluble in water or alcohol, when swallowedget dissolved in the gastric juice and are ultimately absorbed in the guts. The same thing happens in the case of medicines which are insoluble in hydro-alcoholic mixtures, as when they enters in the stomach they get dissolved there in the gastric juice. But it is also known that a few substances, like gold etc., which are insoluble in water or alcohol and also do not dissolve in gastric juice, are also used as medicine. Then what may be the science behind the mechanism of action of these insoluble substances used as medicine and how they get absorbed in the body to affect cure? The scientific reason behind this is the fact that a particle of dimension 10-7 meter or lower can penetrate the cell wall barrier and thus may get absorbed to enter into the blood stream. This happens in case of a colloidal solution, where the suspended particle size is below 10-7meter, and thus Gold sol (a colloidal suspension of gold) is used sometime as a medicine even in the classical or so called modern system.
Keywords: medicine; Trituration; blood stream; hydro-alcoholic